The Attractiveness of Earnings in The Military in The Opinion of Generation Z - Janusz Materac (Communications of International Proceedings, 2021)
The aim of the article was to diagnose the wage attractiveness of the Polish Armed Forces. The article presents the importance of salaries when choosing a profession based on the analysis of source materials. The article describes the employee-oriented payroll feature. The forms of earning money in the Polish Army are discussed in the further part of the work. The methodology of the conducted research and the characteristics of the research group were presented. The result of a pilot study on the attractiveness of earnings in the Polish Armed Forces in the opinion of the Z generation was presented. Conclusions and recommendations resulting from the analysis of the collected research material were presented. The study uses the method of surveying. A questionnaire on the Internet was used, addressed to the representatives of the Z generation.
Keywords: Salaries; soldiers; Generation Z.